Experimental investigation of ventilated partial cavitation. (April 2019) - Qin, Shijie; Wu, Yue; Wu, Dazhuan; Hong, Jiarong
Highlights: Provide a systematic experimental investigation of the ventilated partial cavitation (VPC) across a broad range of flow and ventilation conditions. Reveal the presence of four distinct VPC regimes, and summarize the flow and ventilation conditions corresponding to different regimes on a VPC regime map. Provide a clear physical explanation of the transition across different regimes based on the variation of gas leakage mechanisms. Elucidate the ambiguities present in the current study of VPC from different research groups thorough discussion and comparison of our results with prior studies. Abstract: This study presents the experimental investigation on the cavity regime and the corresponding geometric characteristic of ventilated partial cavitation (VPC). Experiments are conducted in the high-speed water tunnel at Saint Anthony Falls Laboratory. A backward-facing cavitator mounted on the ceiling of test section is used to generate the VPC. The flow filed and the dynamic motion of VPC are captured by the imaging system under varying water speeds and ventilation rates. Four distinct cavity regimes are classified, referred to as foamy cavity (FC), transition cavity (TC), open cavity (OC) and two-branch cavity (TBC). The distribution of these cavity regimes over Froude number ( Fr ) and ventilation coefficient ( C Qs ) is summarized in a regime map with FC and TBC occupying the majority portion of the map. More importantly, the C Qs − F r curves demarcating neighboring cavity regimes are revealed satisfying a clear linear relation for FC–TC and a quadratic relation for TC–OC and OC–TBC when Fr is subtracted with a constant corresponding to the inception condition of the cavity regime. Such trends are attributed to the two gas entrainment mechanisms present in VPC, referred to as recirculating vortex entrainment and cavity closure entrainment. Moreover, the geometric characteristic of VPC characterized by the cavity length is examined. With increasing ventilation at fixed Fr, the cavity length grows linearly in OC regime and remains unchanged in TBC regime. The maximum cavity length of OC is found to be within around 7 times of cavitator height. With increasing Fr at fixed ventilation, the cavity length first grows proportional to Fr 2 in TBC regime but drops sharply with a small increase of Fr when the cavity transitions from TBC to OC. At fixed Fr, the cavity underpressure rises to maximum (minimum σ C ) and stays unchanged in TBC upon increasing ventilation. As a result, in TBC, the cavity length is shown to satisfy a power law relation with respect to Fr or σ C, while in OC, the cavity length is influenced by the interplay among C Qs, σ C and Fr with no clear trend observed.